MENINGKATKAN KUALITAS SDM (SUMBER DAYA MANUSIA) DALAM PENDIDIKAN ISLAM - Afriandi; Sri Rahcamawati Askar; Puput Juliarna Syarif; Nurul Hikmah; Rika Arfiana; Rifda Ningsi; Irawati (TEKNOS: Jurnal Pendidikan dan Teknologi, 2024)
Islamic education in its development process has advantages because of its comprehensive approach, encouraging students to optimize their potential. The goals include religious and worldly aspects, with an emphasis on employability skills in lifelong education. However, achieving this goal requires effectiveness and balanced proportions in the education system. Investment in human resources, including the quality of educators, is important in facing changes in globalization. The concept of human resources developed because humans not only have quantity, but also quality which is influenced by education, experience and values. With the complexity of educational problems and the need to improve the quality of human resources, it is important to continue to develop alternative solutions through Islamic education. Islamic education has a vital function to create individuals who have moral integrity and a high level of professionalism. However, complex challenges such as globalization and technological advances emphasize the need for Islamic education to continue to adapt and improve the quality of human resources to join it. By harmonizing a comprehensive approach that includes developing skills, knowledge, Islamic values, as well as implementing innovative educational technology, Islamic education has the potential to make a significant contribution in improving the quality of human resources. This research also highlights the urgency of investing in training and development of teaching staff, as well as developing curricula that are relevant and responsive to the demands of the times.